(untitled) (International journal of medical sciences, 2026)
Osteoporosis is a metabolic bone disease characterized by a decrease in bone mass and an increased risk of fractures. Bone tissue is a living structure that undergoes continuous remodeling through a balance between bone formation and bone resorption. Under normal physiological conditions, this balance helps maintain bone strength and mineral homeostasis. However, in osteoporosis, normal bone metabolism is disrupted, leading to excessive bone loss. This article aims to explain the physiological mechanisms of bone metabolism and how their disturbance contributes to the development of osteoporosis. The roles of bone remodeling, osteoblast and osteoclast activity, calcium and phosphorus balance, and hormonal regulation are discussed in a step-by-step manner. Special attention is given to age-related and hormonal changes that affect bone physiology. Understanding the normal physiological processes of bone metabolism provides a basis for explaining the pathogenesis of osteoporosis. In addition, this knowledge highlights the importance of preventive measures such as adequate nutrition, physical activity, and hormonal balance, as well as general principles of treatment aimed at restoring bone remodeling balance.